THE NATURE OF EDUCATION AND METHODS OF ISLAMIC EDUCATION - Khoirunnisa Nurfadilah; Siti Nurhamidah; Yurna; Raudatul Janah; Jalaludin Bulkini (Media Inovasi Pendidikan dan Publikasi, 2023)
In Islamic education, the method has a very important position in an effort to achieve goals, because it is a means that gives meaning to the subject matter arranged in the educational curriculum, so that it can be understood or absorbed by students into functional understandings of their behavior. an appropriate method if it contains intrinsic and extrinsic values ​​in line with the subject matter and functionally can be used to realize the ideal values ​​contained in the goals of Islamic education. Between methods, curriculum (materials) and goals of Islamic education contain ideal and operational relevance in the educational process. Therefore, the process of Islamic education contains the meaning of internalizing and transforming Islamic values ​​into the personality of students in an effort to form Muslim individuals who believe in piety and knowledge that practice according to religious guidance and the demands of the necessities of life in society.